Respuesta :

m + n²
 = (2) + (-2)²
 = 2 + 4
 = 6 
answer is A. 6
because negative times negative = positive

Answer:

A.6

Step-by-step expression:

We are given that m= 2 and n=-2

We have to find the value of the expression

[tex]m+n^2[/tex]

To find the value of the given expression we need to substitute m=2 and n=-2 in the given expression

Substitute m=2 and n=-2

Then, we get

[tex]2+(-2)^2=2+4[/tex]

[tex]2+(-2)^2=6[/tex]

Hence, the value of [tex]m+n^2=6 [/tex] when m=2 and n=-2

Answer:A.6